单倍型造血干细胞移植治疗儿童获得性重型再生障碍性贫血的临床研究 (Zhonghua Xue Ye Xue Za Zhi, 2019)
OBJECTIVE: To investigate the efficacy of haplotype hematopoietic stem cell transplantation in the treatment of acquired severe aplastic anemia (SAA) in children. METHODS: The clinical characteristics of 59 pediatric patients with SAA, including 26 cases VSAA, 37males and 22 females, 47 cases typeⅠ and 12 cases typeⅡ, undrerwent haplo-HSCT in our hospital between December 1(st), 2011 and December 1(st), 2017 were retrospectively analyzed. Among 59 patients, 56 patients with a median age of 4.5 (1.2–14.8) years and median weight of 43 (12–80) kg underwent their first HSCT and 3 patients underwent their second HSCT. All patients received the following conditioning regimen: busulfan, cyclophosphamide, and rabbit ATG or Bu (–, CTX), fludarabineand rabbit ATG. The prophylaxis of acute graft versus host disease (aGVHD) was cyclosporine (CsA), MMF and methotrexate. All patients received bone marrow transfusion on day 01 and peripheral stem cell transfusion on day 02 from haploid donor. The median dose of donor mononuclear cell counts was 15.60 (7.74–21.04) ×10(8)/kg of recipient weight and CD34(+) cell counts was 4.86 (3.74–7.14) ×10(6)/kg of recipient weight. RESULTS: Neutrophils and platelets of all 59 children were implanted. The median implantation time of granulocytes and platelets were 13 (10-19) d, 19 (9-62) d, respectively. The incidence of grade Ⅰ-Ⅱ aGVHD was 45.76% (27 cases) and grade Ⅲ/Ⅳ13.56% (8 cases), The incidence of chronic GVHD was 8.47% (5 cases), The incidences of CMV and EBV viremia were 59.32% (35 cases) and 28.81% (17 cases), respectively. The median follow-up was 30 (8–80) months, 57 patients survived with disease free, 2 patients died of GVHD. Both of the estimated 5-year OS and DFS rates were (96.4±2.5) %. CONCLUSION: Haplo-HSCT could improve the outcomes of SAA children.